Analisis Implementasi Kebijakan Insentif Pajak Atas Penghasilan Karyawan Tetap Di Pt Lion Superindo Cabang Pinang Tahun 2021 - Retno Pujianti; Martina Safitry (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
The writing of this thesis aims to find out the implementation of government policies in providing Article 21 Income Tax Incentives that are borne by the government to permanent employees affected by the Covid-19 outbreak and to find out the obstacles and tariffs imposed in companies that are in accordance with government policies. This type of research is a qualitative method with a descriptive study approach. The object of this research is the permanent employees of PT. Lion Superindo that meets the requirements already has a business field classification code listed in the regulation of the minister of finance and is designated as a KlTE company, and has obtained a bonded zone operator permit or a PDKB permit. Based on the Minister of Finance Regulation Number 86/PMK.03/2020 concerning Tax Incentives for Taxpayers Affected by the 2019 Corona Virus Disease Pandemic. The results of the research along with the discussion can be concluded that the substance of the government's policy is to provide incentives for Income Tax Article 21 to be borne by the government based on the Regulation of the Minister of Finance Number 86/PMK.03/2020 concerning Income Tax Article 21 to be borne by the Government on the Income of Workers in Certain Business Categories. The implementation of this tax incentive is given to employees who have a TIN and a permanent gross income of less than 200 million per year. Employees will get additional income in the form of taxes that are not deducted because their tax obligations are borne by the government. Constraints in the delivery of communication and not all employees get income tax incentives article 21 and the calculation is based on PMK no 143 of 2020 and PP number 29 of 2020. This income tax incentive is very useful for employees because they get an increase in take home pay which is obtained from the return of Article Income Tax. 21 to the company no longer depositing Income Tax Article 21 and the tax has been borne by the government.